A LÓGICA EFFECTUAL E OS SEUS PRINCÍPIOS APLICADOS AOS MEIs FRENTE À CRISE ECONÔMICA DO BRASIL (2010-2015): UM ESTUDO DE CASO NA CIDADE DE SÃO BERNARDO DO CAMPO – SP - DIOGO, EVELLYN RUIZ (2016)
In Brazil, entrepreneurship was driven by the opening up of the foreign market, the privatization of large state enterprises, the heating of the domestic economy through the rise of the C and D classes, and the law of the individual microentrepreneur (MEI). Formalization. Individual microentrepreneurs are part of a changing environment and filled with uncertainties, and in this scenario MEI has to make decisions at all times. Thus, this study brings a theory for assimilation, exposing and discussing the theme of strategies of achievement from an Effectuation perspective. The new economic and political scenario is addressed in the fundamental theory, just as there was this decline of entrepreneurship in Brazil, more specifically in the region of Grande ABC, in São Bernardo do Campo, located in the state of São Paulo, from the first Government Dilma Rousseff (from 2010 to 2015). The general objective of this study is to study how a crisis that established itself in Brazil in the period from 2010 to 2015 affected MEIs in the city of São Bernardo do Campo - SP. And how the entrepreneurial strategies on the Efficacy perspective have helped these MEIs to overcome and face a crisis. In order to analyze with the depth of a situation, they were interviewed semi-structured with microentrepreneurs of the city of São Bernardo do Campo - SP. The results show that the interviewed MEIs did not carry out any business plan or any previous study that the assistants in the opening of the store, nor considered a formal study on the subject. Over time, you have a feeling about the business, and have been so happy with a crisis.